Greece and the euro: The chronicle of an expected collapse - Angelos Kotios; George Pavlidis; George Galanos (Intereconomics, 2011)
Ten years after Greece's accession to EMU, the venture has proved to be almost a complete failure. Obviously, the country joined EMU disappointingly unprepared. After EMU accession, Greece failed to seek the necessary adaptations. Its economic policy was inconsistent with the economic logic and rules of the game of a monetary union. EMU did not in itself lead to the Greek crisis. Nevertheless, the supervisory arrangements clearly failed to work. Moreover, the unfolding of the crisis was assisted by EMU's inherent weakness in managing asymmetric disturbances and the absence of early warning and rapid intervention mechanisms.
Keywords: 330